Head-to-Head Comparison of Tau-PET Radioligands for Imaging TDP-43 in Post-Mortem ALS Brain - Knight, Ashley C.; Morrone, Christopher D.; Varlow, Cassis; Yu, Wai Haung; McQuade, Paul; Vasdev, Neil (Molecular imaging and biology, 2023)
Purpose In vivo detection of transactivation response element DNA binding protein-43 kDa (TDP-43) aggregates through positron emission tomography (PET) would impact the ability to successfully develop therapeutic interventions for a variety of neurodegenerative diseases, including amyotrophic lateral sclerosis (ALS).  The purpose of the present study is to evaluate the ability of six tau PET radioligands to bind to TDP-43 aggregates in post-mortem brain tissues from ALS patients. Procedures Herein, we report the first head-to-head evaluation of six tritium labeled isotopologs of tau-targeting PET radioligands, [ 3 H]MK-6240 (a.k.a. florquinitau), [ 3 H]Genentech Tau Probe-1 (GTP-1), [ 3 H]JNJ-64326067(JNJ-067), [ 3 H]CBD-2115, [ 3 H]flortaucipir, and [ 3 H]APN-1607, and their ability to bind to the β-pleated sheet structures of aggregate TDP-43 in post-mortem ALS brain tissues by autoradiography and immunostaining methods. Post-mortem frontal cortex, motor cortex, and cerebellum tissues were evaluated, and binding intensity was aligned with areas of elevated phosphorylated tau (ptau), pTDP-43, and β -amyloid. Results Negligible binding was observed with [ 3 H]MK-6240, [ 3 H]JNJ-067, and [ 3 H]GTP-1. While [ 3 H]CBD-2115 displayed marginal specific binding, this binding did not significantly correlate with the distribution of pTDP-43 and AT8 inclusions. Of the remaining ligands, the distribution of [ 3 H]flortaucipir did not significantly correlate to pTDP-43 pathology; however, specific binding trends to a positive relationship with tau. Finally, [ 3 H]APN-1607 relates most strongly to amyloid load and does not indicate pTDP-43 pathology as confirmed by [ 3 H]PiB distribution in sister sections. Conclusions Our results demonstrate the prominent nature of mixed pathology in ALS, and do not support the application of [ 3 H]MK-6240, [ 3 H]JNJ-067, [ 3 H]GTP-1, [ 3 H]CBD-2115, [ 3 H]flortaucipir, or [ 3 H]APN-1607 for selective imaging TDP-43 in ALS for clinical research with the currently available in vitro data. Identification of potent and selective radiotracers for TDP-43 remains an ongoing challenge.